Counterterrorism in Syria and Iraq: The Issue of ISIS Captives in Detention. Lessons from the Algerian Experience - Khelfa, Nouha (HAPSc Policy Briefs Series, 2023)
This policy brief aims to re-examine the situation of ISIS captives in detention in Iraq and Syria, and the serious security threat that it might pose on the long term, especially, after the loosening of COVID-19 restrictions on movement. This policy brief proposes to extract lessons from the Algerian experience during the 1990s of counterterrorism. The Algerian approach to counterterrorism relies on both the military and the soft method. The Global War on Terror against ISIS was successful militarily, but it lacks the soft method to deal with what comes next to prevent the recreation of new terrorist groups in ISIS concentrated camps. This brief focuses mainly on the Algerian Charter for Peace and National Reconciliation, rebuilding trust, state’s regulations of religion and border protection as effective ways to counterterrorism that can be reproduced in Iraq and Syria.